1997
DOI: 10.1046/j.1365-2249.1997.d01-880.x
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of local Th2-type cytokine mRNA expression in immunocompetent infiltrates in inflamed gingival tissue to periodontal diseases

Abstract: It has been suggested that the types of inflammatory round cell infiltrates and the divergence in the cytokine production profile by macrophages and helper T cells regulate the course of infectious or inflammatory diseases, including periodontitis and gingivitis. We examined the expression of IL‐1α, IL‐1β, IL‐2, IL‐4, IL‐5, IL‐6 and tumour necrosis factor‐alpha (TNF‐α) mRNA in the inflamed gingiva by in situ hybridization. The results of single‐cell analysis were used as data sets for statistical analyses. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
91
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 15 publications
9
91
0
1
Order By: Relevance
“…16 Recent studies have indicated that Th1-dominated responses tend to protect against periodontal tissue destruction, while Th2-dominated responses tend to aggravate the breakdown. 17,18 In a previous study of cellular immunity elicited by PDCM, result showed that PDCM might elicit a delayed type of hypersensitivity in the early stage of wound healing. 14 The ratio of CD4 ϩ/CD8 ϩ cells was 2/1.…”
Section: Introductionmentioning
confidence: 99%
“…16 Recent studies have indicated that Th1-dominated responses tend to protect against periodontal tissue destruction, while Th2-dominated responses tend to aggravate the breakdown. 17,18 In a previous study of cellular immunity elicited by PDCM, result showed that PDCM might elicit a delayed type of hypersensitivity in the early stage of wound healing. 14 The ratio of CD4 ϩ/CD8 ϩ cells was 2/1.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, numerous studies have supported the hypothesis that Th1 cells are associated with stable lesions and Th2 cells are associated with progressive lesions [35][36][37][38][39][40]. In contrast, several studies have demonstrated that upregulation of Th1 responses or downregulation of Th2 responses are involved in periodontal tissue destruction [41][42][43].…”
Section: Cd4mentioning
confidence: 99%
“…Several studies have associated Th1 and Th2 with the etiology of periodontitis [10][11][12][13][14]. Th1 and Th2 are the important components of the immune response which are associated with inflammatory disease and allergic reaction, respectively.…”
Section: Introductionmentioning
confidence: 99%